THE KNOWLEDGE OF EARLY CHILDHOOD EDUCATION TEACHERS ABOUT NATURAL DISASTER MANAGEMENT - Yeni Solfiah; Devi Risma; Hukmi -; Rita Kurnia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
Disaster management